Recommendations from the European Bioanalysis Forum on method establishment for tissue homogenates. (June 2014) - Timmerman, Philip; Mokrzycki, Nathalie; Delrat, Pascal; Meulder, Marc De; Erbach, Eva; Lentheric, Irene; McIntosh, Morna; Dzygiel, Pawel
Tissue analysis has always been a difficult discipline of bioanalysis. Differences in scientific approaches or level of adherence to regulated guidelines have led to a growing ambiguity on how to perform tissue analysis, an ambiguity that starts with the question of if we analyze tissue or tissue homogenates. The European Bioanalysis Forum (EBF) is proposing a recommendation on how to perform method establishment and analysis of tissue homogenates. The recommendation is based on broad discussions and survey data from the EBF community and, as for many EBF recommendations, focuses on finding the right balance between science, technology and regulations.